Anti-hypertensive mechanisms of cyclic depsipeptide inhibitor ligands for Gq/11 class G proteins. (March 2019) - Meleka, Matthew M.; Edwards, Alethia J.; Xia, Jingsheng; Dahlen, Shelby A.; Mohanty, Ipsita; Medcalf, Matthew; Aggarwal, Shaili; Moeller, Kevin D.; Mortensen, Ole V.; Osei-Owusu, Patrick
Graphical abstract: Abstract: Augmented vasoconstriction is a hallmark of hypertension and is mediated partly by hyper-stimulation of G protein couple receptors (GPCRs) and downstream signaling components. Although GPCR blockade is a key component of current anti-hypertensive strategies, whether hypertension is better managed by directly targeting G proteins has not been thoroughly investigated. Here, we tested whether inhibiting Gq/11 proteins in vivo and ex vivo using natural cyclic depsipeptide, FR900359 (FR) from the ornamental plant, Ardisia crenata, and YM-254890 (YM) from Chromobacterium sp. QS3666, or it's synthetic analog, WU-07047 (WU), was sufficient to reverse hypertension in mice. All three inhibitors blocked G protein-dependent vasoconstriction, but to our surprise YM and WU and not FR inhibited K + -induced Ca 2+ transients and vasoconstriction of intact vessels. However, each inhibitor blocked whole-cell L-type Ca 2+ channel current in vascular smooth muscle cells. Subcutaneous injection of FR or YM (0.3 mg/kg, s.c.) in normotensive and hypertensive mice elicited bradycardia and marked blood pressure decrease, which was more severe and long lasting after the injection of FR relative to YM (FRt1/2 ≅ 12 h vs. YMt1/2 ≅ 4 h). In deoxycorticosterone acetate (DOCA)-salt hypertension mice, chronic injection of FR (0.3 mg/kg, s.c., daily for seven days) reversed hypertension (vehicle SBP: 149 ± 5 vs. FR SBP: 117 ± 7 mmHg), without any effect on heart rate. Our results together support the hypothesis that increased LTCC and Gq/11 activity is involved in the pathogenesis of hypertension, and that dual targeting of both proteins can reverse hypertension and associated cardiovascular disorders.